Enhancing Primary Students’ Critical Thinking through School Quality Management Practices and Deep Learning - Asmoni, Asmoni (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study aims to explore how integrating school quality management principles with an immersive learning approach affects elementary school students' critical thinking skills. Using a quasi-experimental design, 80 fifth-grade students from a public elementary school were assigned to an experimental and a control group. The experimental group received instruction aligned with quality management principles and immersive learning, while the control group experienced conventional instruction. Validity and reliability tests confirmed the instrument's suitability (CVI = 0.93; α = 0.87). Results showed a significant improvement in the experimental group (t = 10.518, p < 0.001; N-gain = 0.56, moderate) compared to the control group (N-gain = 0.22, low). This study is innovative because previous research generally examines school quality management or immersive learning separately and at higher education levels, whereas this study integrates both in elementary education. Theoretically, this study extends the educational management literature by validating the pedagogical dimensions of quality management. Practically, this study provides guidelines for schools to align quality management practices with classroom-based immersive learning to develop students' critical thinking.